Market Valuation and Acquisition Quality: Empirical Evidence - Bouwman, Christa H. S.; Fuller, Kathleen; Nain, Amrita S. (Review of Financial Studies, 2009)
Existing research shows that significantly more acquisitions occur when stock markets are booming than when markets are depressed. Rhodes-Kropf and Viswanathan (2004) hypothesize that firm-specific and market-wide valuations lead to an excess of mergers, and these will be value destroying. This article investigates whether acquisitions occurring during booming markets are fundamentally different from those occurring during depressed markets. We find that acquirers buying during high-valuation markets have significantly higher announcement returns but lower long-run abnormal stock and operating performance than those buying during low-valuation markets. We investigate possible explanations for the long-run underperformance and conclude it is consistent with managerial herding. The Author 2007. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For permissions, please e-mail: journals.permissions@oxfordjournals.org., Oxford University Press.